Metformin in gynecological disorders: pathogenic insights and therapeutic implications - Nie, Ping; Wang, Minghua; Mo, Yan; Zhou, Hong; Zha, Qingbing; Lash, Gendie E.; Li, Ping (Frontiers in Pharmacology, 2025)
Metformin, the most widely used anti-diabetic drug, has been demonstrated to exert various effects, including antioxidant, anti-inflammatory, anti-tumor, and cardioprotective properties. Due to its affordability and low toxicity profile, metformin is increasingly used to prevent or treat a wide range of gynecological disorders, as evidenced by epidemiological studies, clinical trials, and animal and in vitro studies. Trial findings for non-cancer conditions such as endometriosis, premature ovarian failure (POF), and uterine fibroids remain controversial and insufficient. However, most current clinical trials for polycystic ovarian syndrome (PCOS) and gynecological malignancies are ongoing phase II–III trials. The pharmacological effects of metformin have been shown to target the insulin-like growth factor (IGF), AMP-activated protein kinase (AMPK), phosphatidylinositol 3-kinase (PI3K)/AKT, MAPK, NF-κB, and other signal transduction pathways, highlighting its potential in the treatment of gynecological disorders. In this review, we discuss the biological impacts of metformin and the mechanisms of action pertinent to the treatment of different gynecological disorders.